Weir Do - Do, Anh; Faber, Jules, 1971- (2013)
Weir Do's the new kid in school. With an unforgettable name, a crazy family and some seriously weird habits, fitting in won't be easy but it will be funny!
For primary school age.
Keywords: Names, Personal -- Juvenile fiction; Humorous stories; Children's stories